The efficiency of the ivermectin and its effects on the status of the antioxidant system and lipid peroxidation in rabbits infested with mites psoroptes cuniculi - Юськів, І. Д.; Шидер, Є. І. (Scientific Progress & Innovations, 2018)
Psoroptosis is an invasive disease of rabbits caused by ear mange mites Psoroptes cuniculi. The disease leads to weight loss in rabbits, mortality of young animals, deterioration of the quality of fur and causes significant economic damage to farms. Consequently, it is appropriate to develop technically simple, cheap and effective treatment of psoroptosis in rabbits. In addition, at the present stage of formation of a well-off system for the keeping rabbits and the European Convention for the Protection of Animals, there is necessity to minimize pain and distress factors. The purpose of our research is to determine the effectiveness of Profiverm 1% (O.L.KAR., Ukraine) for rabbits infested with ear mites Ps. cuniculi with local and systemic application. The research objective is to determine the effect of ivermectin-based drug on the level of antioxidant enzymes and lipid peroxide oxidation. It has been found that the Profiverm 1% (O.L.KAR., Ukraine) on the basis of ivermectin is effective at doses of 200 mcg and 400 mcg (E = 100%) for rabbits infected with Psoroptosis. The efficacy of Profiverm 1% (O.L.KAR., Ukraine) for systemic and topical application for rabbits infected with Psoroptosis has high therapeutic effectiveness (E = 96-100%). It has been found that the level of enzymes of the antioxidant system (catalase and superoxide dismutase) and lipid peroxidation products (malonic dialdehyde and diene conjugates) indicate faster reversal of oxidative processes organism following topical administration of ivermectin than with subcutaneous injections in rabbits infested with ear mites Ps. cuniculi.